Neurotrophic effects of neudesin in the central nervous system - Kimura, Ikuo; Nakayama, Yoshiaki; Zhao, Ying; Konishi, Morichika; Itoh, Nobuyuki (Frontiers in Neuroscience, 2013)
Neudesin (neuron-derived neurotrophic factor; NENF) was identified as a neurotrophic factor that is involved in neuronal differentiation and survival. It is abundantly expressed in the central nervous system, and its neurotrophic activity is exerted via the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways. Neudesin is also an anorexigenic factor that suppresses food intake in the hypothalamus. It is a member of the membrane-associated progesterone receptor (MAPR) family and shares key structural motifs with the cytochrome b5-like heme/steroid-binding domain. Progesterone receptor membrane component 1 (PGRMC1), the first to be discovered among the MAPR family, binds progesterone to induce “rapid non-genomic effects” in biological responses that are unrelated to the nuclear progesterone receptors (PRs). Hence, neudesin may also be involved in the rapid non-genomic actions of progesterone. In this review, we summarize the identification, structure, and activity of neudesin in the central nervous system, and present an essential overview of the current understanding of its physiological roles and the prospect of elucidating its non-genomic progesterone effects.